Incidence and predictors of mortality among low birth weight neonates admitted to neonatal intensive care unit in selected public hospitals, North Shoa zone, Amhara Region, Ethiopia: multi-center retrospective follow-up study - Mengstie, Leweyehu Alemaw; Gebeyehu, Mohammed Tessema; Zeneb Teklehaimanot, Wegayehu; Shibabaw Shiferaw, Wondimeneh; Kebede, Tirusew Nigussie; Abemie, Worku; Girma, Bekahegn (Frontiers in Pediatrics, 2025)
BackgroundBirth weight of less than 2,500 g is the leading cause of neonatal morbidity and mortality. Various studies in developed and developing countries examine the prevalence and associated factors. However, little is known about low birth weight neonatal incidence and predictors of Mortality in Ethiopia.ObjectiveThe study aimed to assess the incidence and predictors of mortality among low birth weight neonates admitted to the neonatal intensive care unit at a public hospital, in Northeast, Ethiopia, 2021.MethodsAn institution-based retrospective follow-up study was conducted among 416 low-birth-weight neonates admitted to the neonatal intensive care unit from January 1, 2019 to December 30, 2021. Epi-data version 3.1 was used for data entry and Stata14 software for analysis. The Kaplan–Meier survival curve and the Log-rank test were used to estimate the cumulative survival time and compare the probability of survival time among variables. Multi-variable and bi-variable Cox proportional hazard model was used to identify predictor variables.ResultsOut of 416 Low birth weight neonates, 107 (25.72%) (95% CI: 21.51, 29.93) of them died. The overall incidence rate of mortality was 42.83 per 1,000 (95% CI: 35.34, 51.77) with 2,498 person-days of observation. Twin pregnancy [adjusted hazard ratio (AHR): 1.7 (95% CI: 1.42, 3.29)], Sepsis (AHR: 1.5; 95% CI: 1.01, 2.32), respiratory distress syndrome (AHR: 1.6; 95% CI: 1.15, 2.68), maternal history of HIV (AHR: 2.2; 95% CI: 1.54, 3.42), maternal DM (AHR: 2.5; 95% CI: 1.70, 3.87) and preeclampsia (AHR: 1.8; 95% CI: 1.23, 2.73) were found to be significant predictors of low birth weight (LBW) neonatal mortality.ConclusionThe incidence rate of low birth weight neonatal mortality was high and continues as a public health issue. Therefore, special attention should be given to those identified predictors of mortality, and different measures should be implemented to prevent premature birth in the high-risk population by improving prenatal care.